2019
DOI: 10.24203/ajas.v7i2.5606
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Economic Growth and Environmental Degradation in Nigeria using Vector Auto-Regressive Model

Abstract: The study examined the interrelationship among economic growth, environmental pollution and human health for Sustainable Development (SD) in Nigeria. This was to contribute to the dynamic debate of how human and economic activities relate and interrelate with environmental pollution in measuring sustainable development in Nigeria. This study further sought to verify the Environmental Kuznet Curve Hypothesis in Nigeria.The study employed the Vector Error Correction Model (VECM) to investigate linear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…P is obtained from a Choleski decomposition being a lower positive triangular matrix) (the packages used in R to perform all the analysis were: "tsDyn" [26], "forcats" [27], "stringr" [28], "dplyr" [29], "purrr" [30], "readr" [31], "tidyr" [32], "tibble" [33], "ggplot2" [34], "tidyverse" [35], "kableExtra" [36], "readxl" [37], "forecast" [38], "knitr" [39], "car" [40], "carData" [41], "broom" [42], "nlWaldTest" [43], "vars" [44], "lmtest" [45], "urca" [46], "strucchange" [47], "sandwich" [48], "MASS" [49], "dynlm" [50], "zoo" [51], "tseries" [52]) [53]. This model has been widely used in Rehman et al (2019) [54], Olatayo, T. O., (2019) [55], Flores de Frutos, et. al.…”
Section: Methodsmentioning
confidence: 99%
“…P is obtained from a Choleski decomposition being a lower positive triangular matrix) (the packages used in R to perform all the analysis were: "tsDyn" [26], "forcats" [27], "stringr" [28], "dplyr" [29], "purrr" [30], "readr" [31], "tidyr" [32], "tibble" [33], "ggplot2" [34], "tidyverse" [35], "kableExtra" [36], "readxl" [37], "forecast" [38], "knitr" [39], "car" [40], "carData" [41], "broom" [42], "nlWaldTest" [43], "vars" [44], "lmtest" [45], "urca" [46], "strucchange" [47], "sandwich" [48], "MASS" [49], "dynlm" [50], "zoo" [51], "tseries" [52]) [53]. This model has been widely used in Rehman et al (2019) [54], Olatayo, T. O., (2019) [55], Flores de Frutos, et. al.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the results consistently show that energy consumption is the main cause of CO2 emissions. Olatayo et al (2019) examined the annual time series data between 1970 and 2015 with a VECM instrument. The study found a mixed interrelationship between economic growth and environmental degradation.…”
Section: Literature Review Theoretical Literaturementioning
confidence: 99%